COMPUTER MODELING IN CAE «PROTERM-1» OF HEAT TREATMENT OF PRODUCTS IN A GIVEN FURNACE HEATING MODE - A. N. Chichko; D. M. Kukuу; V. F. Sobolev; S. G. Lihouzov; O. A. Sachek; O. I. Chichko (Литьë и металлургия)
The numerical modeling of process of the steel casting “Link” heat treatment for the set mode of heating is carried out by means of the developed module of heating. Dependences of statistical parameters of temperature field on heating time for the purpose of carrying out quantitative assessment of various groups of net elements in relation to the average temperature of an object are calculated.